Penentuan Kadar Selenium dalam Suplemen Kesehatan dengan Metode Spektrofotometri Menggunakan Reagen Kolorimetri 2,3-Diaminonaftalena - Gumilar, Anggi; Putri, Adinda Triani; Dewi, Mira Andam; Ibrahim, Slamet (School of Pharmacy Institut Teknologi Bandung, 2025)
Health supplements containing selenium are now increasingly used by public . However, so far, a simple analytical method for determining selenium in health supplements are still rare. The latest method for determining selenium is based on Inductively Coupled Plasma (ICP) spectrometry. The cost of this method is very expensive. This study aims to apply and validate the UV-Vis Spectrophotometry method for determining selenium in health supplements using 2,3 Diaminonaphthalene as reagent. The study began by testing the specificity of reaction between Selenium with the reagent, that it is showed in specific spectrum with maximum absorbance wavelength at 483 nm. The linearity test using calibration curve, the results obtained were a linear regression equation y = 0.0126x + 0.0736 with the value of r2 = 0.9974 and Vx0 = 0.01%. Limit of detection = 0.00917 mg/mL and limit of quantitation = 0.02777 mg/mL. The accuracy of this method expressed as an average of % Recovery was 97.84% and the precision expressed as % RSD was 0.02%. The final step of this study was the determination of selenium in supplement samples using the standard addition method. The average results obtained based on the determination of selenium levels in supplements were 58.82% (sample A); 111.17% (sample B); and 98.08% (sample C) calculated against the selenium levels listed on the label of each sample, namely 25, 30, and 50 mg Se, with the requirement being in the range of 90 - 110% of the levels listed on the label. Thus, only sample C meets the requirements.